Distribution and density of avifauna in Península de Osa, Costa Rica (1990-1991). - Pereira, Ana I (2009)
We recorded 205 bird species at the Península de Osa. The geographical distribution of most forest bird species within the peninsula is discontinuous (e.g., Corapipo altera and Tangara guttata), even within large forest tracts, indicating the adaptation of species to particular habitats, microhabitats, strata and/or diet within the forest. Birds use the forest strata in different proportion resulting in three different patterns: understory birds (e.g., Arremon aurantiirostris and Habia atrimaxillaris), supdosel birds (e.g., Cacicus uropygialis and Euphonia imitans), and birds that use several strata in similar proportion (e.g., Dendrocincla anabatina). Most of these forest birds feed upon insects and fruits. The density and relative abundance is very low for most species, with more than 90% of the species having less than an individual per hectare or kilometer of transect. These characteristics make this avifauna highly susceptible to deforestation and forest fragmentation.